Evaluating Netflix's User Experience (UX) Through The Lens Of The HEART Metrics Method - Astriani, Yulia; Indah, Dwi Rosa; Utari, Meylani; Syahbani, M Husni (Journal of Applied Informatics and Computing, 2024)
Netflix is one of the most popular subscription video-on-demand (SVoD) platforms, offering a wide range of authentic, high-quality content and features that allow users to select, enjoy, and share their viewing experiences on social media. Despite its popularity, Netflix often receives complaints from users, including issues with accessing the application and various features related to viewing activities. The aim of this study is to evaluate the user experience of the Netflix application and provide recommendations for improvement based on data analysis. To achieve this, the HEART Metrics are utilized, which focus on the user's perspective, and apply the Importance-Performance Analysis (IPA) method to map performance and identify improvement priorities. The research reveals several areas that require enhancement, particularly three priority variables: the Happiness variable (Hp3), indicated by the statement "I like the appearance of the Netflix application"; the Retention variable, represented by "I enjoy using the features of the Netflix application"; and the Task Success variable (Ts4), reflected in "I can save movies in the Netflix application." To improve user satisfaction, Netflix can incorporate both light and dark themes, creating a more user-friendly interface. This update could enhance navigation, increase time spent on the platform, promote recommendations, and encourage subscription renewals.